Biopathology of astrocytes in human traumatic and complicated brain injuries. Review and hypothesis - Castejón, Orlando José (Folia Neuropathologica, 2015)
The biopathology of astrocyte cells in severe human brain traumatic injuries complicated with subdural and epidural haematoma and hygroma is reviewed. Clear and dense oedematous and hypertrophic reactive astrocytes are distinguished in severe primary traumatic vasogenic and secondary cytotoxic brain oedema. Swollen perineuronal astrocytes appear compressing and indenting clear and dark degenerated pyramidal and non-pyramidal nerve cells, degenerated myelinated axons and synaptic contacts. Hypertrophic astrocytes display dense cytoplasm and contain numerous rosettes of alpha, beta- and gamma-type glycogen granules, swollen mitochondria, dilated smooth and rough endoplasmic reticulum, oedematous Golgi apparatus, microtubules, gliofilaments, intermediate filaments, lysosomes and liposomes. The perisynaptic astrocyte ensheathment of synaptic contacts, containing beta type-glycogen granules, can be traced in the neuropil, surrounding swollen, bead-shaped dendritic profiles, and degenerated myelinated axons. This perisynaptic glial layer is absent in severe oedematous regions. The glycogen-rich and glycogendepleted perivascular astrocyte end-feet appear attached or dissociated from the capillary basement membrane. Phagocytic astrocytes can be seen engulfing degenerated synaptic contacts, necrotic membranes, degenerated myelinated axons, and myelin ovoids. Lipofuscin-rich astrocytes are also observed. The interastrocytary gap junctions appear either widened, fused or fragmented. The key role of aquaporin in astrocyte swelling and brain oedema is emphasized. The findings are compared with those reported in experimental traumatic animal models, a large variety of pathogenetically related neuropathological conditions, and in vivo and in vitro experimental conditions. The contribution of pathological astrocytes to neurobehavioral disorders, such as loss of consciousness, neurological deficits and seizures is emphasized. Some hypotheses are postulated related to the dissociated or absent perisynaptic layer, neurobiology of glycogen-rich and glycogen-depleted perivascular astrocytes, the glio-basal dissociation process, abnormal astrocyte-neuronal unit, and astrocyte participation in seizures in patients with severe and complicated brain injuries.